Equality and Education: Federal Civil Rights Enforcement in the New York City School System - MICHAEL A. REBELL, ARTHUR R. BLOCK (Princeton University Press, 2014)
In 1974, the Office for Civil Rights of the United States Department of Health, Education and Welfare announced that it would initiate a massive, new, computer-based investigative approach to probe patterns of civil rights compliance in large urban school systems. The prototype for this ambitious project was the "New York City Review," which was to become "the largest civil rights investigation of a public education institution ever undertaken."1 This new investigative technique was expected to open up entirely new possibilities for civil rights enforcement. To some extent it did. But, at the same time, it also revealed fundamental limitations in OCR's institutional functioning and significant ambiguities in the egalitarian statutes the agency was attempting to enforce. The legal underpinning of the reviews is contained in Title VI of the 1964 Civil Rights Act. In seemingly simple language, Title VI prohibits discrimination on the basis of race, color, or national origin in any program or activity receiving federal financial assistance. At the time this law was passed, Congress's focus was on the elimination of the de jure dual school systems in the South that had been declared unconstitutional ten years earlier by the Supreme Court in Brown v. Board of Education.2 Defining discrimination in this context was a relatively straightforward task. By 1972, however, after the most blatant violations of Brown's mandate had been eliminated and the civil rights focus had moved on to more subtle discrimination problems in both the South and the North, identifying discrimination became more difficult. Neither the language of Title VI nor its legislative history provided clear standards for this new phase of civil rights enforcement.